The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fnins.2020.00592
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Functional and Causal Connectivity in Acute Tinnitus With Sensorineural Hearing Loss

Abstract: The neural bases in acute tinnitus remains largely undetected. The objective of this study was to identify the alteration of the brain network involved in patients with acute tinnitus and hearing loss. Methods: Acute tinnitus patients (n = 24) with hearing loss and age-, sex-, education-matched healthy controls (n = 21) participated in the current study and underwent resting-state functional magnetic resonance imaging (fMRI) scanning. Regional homogeneity and amplitude of low-frequency fluctuation were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…The index of this interpretation was the MMN. In accordance with the present investigation, a recent study found aberrant functional connectivity in the auditory and non-auditory cortex, especially in the superior temporal gyrus (Cai et al, 2020). Other studies suggested different interpretations of the cause of tinnitus occurrence.…”
Section: Discussionsupporting
confidence: 93%
“…The index of this interpretation was the MMN. In accordance with the present investigation, a recent study found aberrant functional connectivity in the auditory and non-auditory cortex, especially in the superior temporal gyrus (Cai et al, 2020). Other studies suggested different interpretations of the cause of tinnitus occurrence.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, this is the first study to identify the central processing network and neural predictors for the development of tinnitus by using source localization and functional connectivity methods. Although a number of previous studies on chronic tinnitus have been published and many pathophysiological models have been developed (Chen et al, 2017; Chen et al, 2018; Vanneste, Song, & De Ridder, 2018; Vanneste, To, & De Ridder, 2019), few studies have investigated central plasticity in acute tinnitus (Cai et al, 2019; Cai et al, 2020), especially the dynamic changes to neural processing in the transition period from acute to chronic tinnitus. This issue is crucial to clarify central neural characteristics of acute and chronic tinnitus, which is important in identifying neural predictors for the development of tinnitus and prevent transition from acute to chronic.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of previous studies on chronic tinnitus have been published and many pathophysiological models have been developed, few studies have investigated central plasticity in acute tinnitus (Cai et al, 2020; Stolzberg et al, 2013), especially the dynamic changes to neural processing during transition from acute to chronic tinnitus. This issue is crucial to clarifying the central neural characteristics of acute and chronic tinnitus, which is important in identifying neural predictors for the development of tinnitus and prevention of transition from acute to chronic tinnitus.…”
Section: Introductionmentioning
confidence: 99%
“…However, some recent studies reported no significant difference in the ReHo value between the ISSNHL patients and the healthy controls in any brain region. The various neuroimaging methods employed and the participants’ heterogeneity may have contributed to the inconsistent results ( Cai et al, 2020 ; Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%